“The threat of being Morganized will not deter us”: William Lyon Mackenzie, Freemasonry and the Morgan Affair - Raible, Chris (Ontario History)

(untitled) (The Ontario Historical Society, 2008)
In January 1827 William Lyon Mackenzie applied for membership to in York’s lodge of Freemasons, an episode in his life totally ignored by his biographers. His action seems incompatible with the character and personality of the radical journalist. As he was re-establishing his printing business in the wake of its blatant destruction, why would Mackenzie, an outsider, want to join the Masons, the insiders? And why would the Masons consider welcoming him into their secret circle? Freemasonry was embroiled in sandal over the abduction and supposed murder of William Morgan, author of a book exposing Masonic secrets. Mackenzie began publishing lurid stories of the Morgan affair. The Masons rejected his membership application. Mackenzie proceeded to put out his own edition of Morgan’s book. A mutually beneficial bargain, exchanging editorial silence for social status had failed – and Mackenzie published his version of the drama in the columns of the Colonial Advocate.